Application of the Piercing the Corporate Veil Doctrine in the Accountability of the Board of Directors Linked to Law Number 40 of 2007 concerning Limited Liability Companies - Moh. Asep Suharna (Budapest International Research and Critics University, 2022)
The purpose of this paper is to analyze the position of the Board of Directors in a Limited Liability Company according to Law Number 40 of 2007 concerning Limited Liability Companies, and the application of the Piercing the Corporate Veil doctrine in the accountability of the Board of Directors in relation to Law Number 40 of 2007 concerning Limited Liability Companies. The research method used in this research is descriptive analytical, with a normative juridical approach. This research was conducted by means of library research and field research with data collection techniques through documentation studies and interviews as well as data analysis methods used in this study using qualitative juridical analysis. Based on the results of the discussion above, it can be concluded: First, UUPT to some extent acknowledge the validity of this theory of Piercing the Corporate Veil. The application of this theory to the actions of a company causes legal responsibility not only to be requested from the company (even though it is a legal entity), but legal liability can also be requested from its shareholders, Directors or Commissioners. Second, The actions of the Board of Directors which are not based on the principle of fiduciary duty that cause losses to the PT, the Board of Directors can not only be fully responsible personally for the losses that occur in accordance with Article 97 paragraphs (3) and (4) of the Company Law, the Board of Directors must be responsible for the losses incurred by the company due to his or her mistakes and omissions.